INDUCTION CALLUS OF MORINGA PLANT (MORINGA OLEIFERA) IN VITRO - Abdul-Sadah, Zahraa Abbas trad; Ahmed, Rahma Abd Al gabar; Fadhel, Sarah Salam Talib; Ibrahim, Mohammed Allawi Abed; Jiyad, Nawras Saadoun Majbas (PT. Antis International Publisher, 2024)
This study aims to find an easy and efficient way to induce callus tissue of (Moringa oleifera) in vitro. The seeds were used as explant for cultivation in vitro, these parts were sterilized with sodium hypochlorite (Naocl) at concentrations (0.0, 0.5, 1.0, 2.0%) for a period of time (5,10 ,15, 20 minutes) and mercury chloride solution 0.06,0.07,0.08 0.1 mg/L) and for a period of time (2,3,4,5 minutes). Explant were planted in the medium (Murashige and Skoog (MS) in addition to different concentrations of plant growth regulators (BA, NAA), either individually or in combination. The results showed that the use of sodium hypochlorite solution (NaocL) with a concentration of 2% and a sterilization period of 20 minutes gave the highest sterilization rate of 100% without causing damage to the plant part. Also, the seeds produced callus after 48 days of culture on Ms medium containing the best combination of plant growth regulators (BA 4.0, NAA 0.5 mg/L)